Exploring Sound Waves through a Frequency Study of the Ambience Music Weightless by Marconi Union - Andriyanto, R.M. Aditya; Budiawan, Hery; Safrina, Rien; Rahman, Putri Safrani; Fredlina, Oriana Aisha; Putri, Lara Heltna Yuma (Gondang: Jurnal Seni dan Budaya, 2024)
This study explores the creation process of "Weightless," a relaxation music piece by Marconi Union, with a focus on its compositional elements and how frequencies are manipulated. The aim is to deepen the understanding of both educators and undergraduate students regarding the use of Digital Audio Workstations in composing music, thereby promoting digital literacy within 21st-century music education. The research employs a descriptive qualitative method, utilizing an exploratory approach and content analysis.Through this analysis, it becomes clear that "Weightless" effectively incorporates slow tempos, minimalistic textures, and gradual changes in dynamics to create a relaxing atmosphere. The frequency analysis highlights the importance of low frequencies (ranging from 20 to 200 Hz), which contribute to a sense of depth and tranquility. In contrast, mid and high frequencies are carefully balanced to ensure they do not overwhelm the listener. Additionally, the loudness analysis reveals a smooth dynamic range, with an average level of -13.9 LUFS and no sudden peaks, which guarantees a pleasant listening experience across various playback devices. Overall, these findings emphasize the critical role of precise frequency manipulation and loudness control in producing effective relaxation music, providing valuable insights for both music composition and education.